Combined use of SA‐XPS, XRD and SEM + EDS for the micro‐chemical characterisation of Ag‐based archaeological artefacts1. (29th January 2014) - Mezzi, A.; Riccucci, C.; de Caro, T.; Angelini, E.; Faraldi, F.; Grassini, S.; Gouda, V. K.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The precious metallic artefacts are particularly interesting from a historical, artistic and economical point of view because they were used as jewels, amulets or artistic items and also for currency, medium of exchange and form of saving. By means of the combined use of XPS, X‐ray diffraction, SEM + energy dispersive spectrometry and optical microscopy, the micro‐chemical surface structure of the corrosion products grown on archaeological Ag‐based artefacts has been investigated in the present work. The obtained results allowed the identification of the corroding agents coming from the surrounding environment where the artefacts have been found, stored or exhibited. The experimental findings highlight the role of chloride ions that are present in the patina as chloroargyrite or corrode the copper islands scattered in the alloy giving rise to the formation of the dangerous species such as atacamite and paratacamite. Furthermore, the results shown different corrosion behaviours with the outermost layers enriched of S, Ca, Al, Si and Fe demonstrating the relationship between some soil constituents and surface alloy corrosion products giving rise to the formation of different compounds. Copyright © 2014 John Wiley & Sons, Ltd.